SIGNIFIKANSI FARSY AL-HURUF DALAM SURAH AL-FATIHAH DAN IMPLEMENTASINYA DI KALANGAN MAHASISWA ILMU AL-QURAN DAN TAFSIR - Ina Salmah Febriani; Nurhasana; Mustafakama Waduereh (Qiro'ah : Jurnal Pendidikan Agama Islam, 2025)
Knowledge of the variations in the recitation of the Qur'an is increasingly important for students to read and practise the seven types/faces (variations) of the seven imams of qiraat (qiraah sab'ah). It is not only important to know the recitation of one Imam—such as Imam Hafsh, who is popular in Indonesia—but also the variations in the recitation of other imams of qiraat, such as Imam Nafi' and Imam Abu 'Amr, especially in this digital age. The speed of technology needs to be balanced by knowledge of the recitations of the seven imams to equip students with the knowledge so that they do not get caught up in recitation errors or specific rules (farsy al huruf). However, not all students have the ability to study this science of qiraat. Therefore, the author raises the theme of the significance of farsy al-huruf in the recitation of the seven imams in Surah Al-Fatihah for students of the Al-Quran and Tafsir Study Programme. Surah al-Fatihah was chosen because it is recited repeatedly every day in a five daily prayer. A qualitative research methodology was chosen for this study because the researcher had to conduct in-depth interviews with students to determine their level of knowledge regarding farsy al-huruf qiraat sab'ah, especially in Surah al-Fatihah. In general, students are aware of the various readings and farsy al-huruf qiraat imam tujuh in Surah Al-Fatihah, but many of them do not know where the differences, and some of them have never studied qiraat before.